Indicadores financieros que explican la rentabilidad de la caja municipal de ahorro y crédito de Maynas en el periodo 2018-2022 - Cubas Alvarado, Ada Edith (2024)
The present research is of a quantitative nature, characterized by a descriptive-causal level and a non-experimental design with longitudinal data. It included, as the study population, the monthly records on financial indicators of CMAC Maynas from January 2018 to December 2022. The objective was to identify the financial indicators explaining the profitability of CMAC Maynas during the observed period. The results, obtained through the application of a multiple regression model for time series, demonstrate that administrative expenses, operating expenses, provisions for overdue credits, and the evolution of direct credits with a lag of six periods explain 82.71% of the monthly variations in the profitability level of CMAC Maynas during the period 2018-2022.